Estimating the properties of a fine aggregate fibre reinforced cementitious composite using non-destructive methods - Głodkowska, Wiesława; Kobaka, Janusz (Journal of Civil Engineering and Management, 2018)
The paper proposes a method of estimating the properties of a fine aggregate steel fibre reinforced cementitious composite using non-destructive methods. Two methods were selected to identify the properties of such a composite. One of them uses electromagnetic induction in order to estimate the content of steel fibres dispersed in the composite space, while the other is based on the determination of ultrasonic wave velocity propagating through the composite. Having defined correlations between the properties of the fibre reinforced composite and non-destructive testing parameters, regression equations were determined. Seven relationships between properties of fibre reinforced composite as the dependent variables and two independent variables, i.e.: amperage and ultrasonic wave velocity, were established. Knowing the amperage and the ultrasonic wave velocity, the basic properties of the fibre reinforced composite can be determined from the regression equations in a non-destructive manner. In order to verify the equations, three plates with different amounts of steel fibres were made in field under natural conditions, and next subjected to non-destructive tests. The tests showed good compatibility between the experimental results and those of calculations, which indicates the correctness of the formulated equations.